2018
DOI: 10.20892/j.issn.2095-3941.2018.0022
|View full text |Cite
|
Sign up to set email alerts
|

ATM in breast and brain tumors: a comprehensive review

Abstract: The ATM gene is mutated in the syndrome, ataxia-telangiectasia (AT), which is characterized by predisposition to cancer. Patients with AT have an elevated risk of breast and brain tumors Carrying mutations in ATM, patients with AT have an elevated risk of breast and brain tumors. An increased frequency of ATM mutations has also been reported in patients with breast and brain tumors; however, the magnitude of this risk remains uncertain. With the exception of a few common mutations, the spectrum of ATM alterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 170 publications
0
7
0
Order By: Relevance
“…Interestingly, the other three germline mutated genes (ATM, ERCC4, and POLE) are all involved in the DNA damage repair pathway ( 61 ), which are key factors in maintain genomic integrity and stability. Germline mutations in ATM gene are thought to contribute to breast cancer susceptibility ( 62 ). And previous study suggested germline mutations affecting the exonuclease domain of POLE predispose to CRC and endometrial cancer ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the other three germline mutated genes (ATM, ERCC4, and POLE) are all involved in the DNA damage repair pathway ( 61 ), which are key factors in maintain genomic integrity and stability. Germline mutations in ATM gene are thought to contribute to breast cancer susceptibility ( 62 ). And previous study suggested germline mutations affecting the exonuclease domain of POLE predispose to CRC and endometrial cancer ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…ATM kinase activates cell cycle arrest, DNA repair, or apoptosis to restore proliferation of normal cells and maintain genomic stability, or eliminate heavily damaged cells. The loss of ATM kinase causes ataxia-telangiectasia, a syndrome associated with increased chromosomal abnormalities and high predisposition to breast cancer, brain cancer, lymphoma, and leukemia ( Treuner et al, 2004 ; Estiar and Mehdipour 2018 ). Lieberman et al showed that RAD52 deletion in Squamous Cell Lung Carcinoma increased the death of cells undergoing carcinogen-induced transformation in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…ATM is activated in response to DSB and plays a role in repairing the DNA damage by recruiting proteins, signalling the cell checkpoint and inducing apoptosis (Ref. 39). The role of ATM in phosphorylating various compounds (p53, CHK2, H2AX), thus inducing the cell cycle arrest and apoptosis is well-known (Refs 31, 34).…”
Section: Ddr Pathway Statut In Gbmmentioning
confidence: 99%